Rola i zadania psychologa szkolnego = The role and functions of an educational psychologist - Frąckowiak, Tomasz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article is a synthetical guide for psychology students and beginner psychologists who plan to work in educational institutions. It also serves as a point of reference for professionally active educational psychologists who would like to verify and complete the range of activities they perform. The functions of a psychologist described in the paper may also be of a point of interest for pedagogues, teachers and parents who would like to acquire a better understanding of a kind of help they may expect from an educational psychologist. The article constitutes the characteristics of a school psychologist?s work in relation to an individual student and the whole class, as well as the psychologist?s cooperation with teachers and parents. Moreover, it describes the legal basis of psychological assistance provided at school, the documentation and record keeping.
Keywords: psycholog; szkoła; uczniowie; rodzice; nauczyciele; education; school; teachers; students; parents